Impact of Socioeconomic Inequalities on the Incidence of Type 2 Diabetes Mellitus: A Systematic Review - Calvin Sasongko; Jessica Adrya; Srigita Varsha; Sony A. Fatchurrahman; Galih Muchlis Hermawan; Veriantara Satya Dhika; Teddy Tjahyanto; Natania Eliadi (Medicinus, 2026)
ckground: Type 2 diabetes mellitus (T2DM) is a rising global burden, and socioeconomic inequalities may shape risk through differential resources, environments, and access to prevention and care. We synthesised evidence on the association between socioeconomic position (SEP) and incident T2DM. Methods: We conducted a PRISMA 2020–guided systematic review of PubMed, EMBASE, and Scopus (inception to 18 January 2026). Observational studies of adults without diabetes at baseline that measured SEP (education, income, occupation and/or area deprivation) prior to diagnosis and reported incident T2DM were eligible. Random-effects meta-analyses pooled relative risks (RRs), treating hazard ratios as approximations. Risk of bias was assessed (NOS). Result: From 1,580 records, 25 studies met inclusion criteria and 23 contributed to quantitative synthesis. Studies were mainly prospective cohorts or nested case–control designs, largely from high-income countries, with follow-up from 3 to 34 years and participants aged 18–86 years. Lower education was associated with higher T2DM incidence (least vs most educated: RR 1.55, 95% CI 1.37–1.75). Lower occupational position was also associated with increased risk (lowest vs highest: RR 1.60, 95% CI 1.25–2.05). Income was not statistically conclusive (lowest vs highest: RR 1.37, 95% CI 0.94–2.01). Conclusions: Socioeconomic disadvantage, particularly lower education and occupational status, is consistently associated with higher risk of incident T2DM. Prevention and screening should incorporate SEP to better target upstream determinants.